Intertextualidad en el cuento “El Extraño viaje” de la escritora ecuatoriana Gabriela Alemán. - Zula Colcha, Joselyn Estefania (2023)
The research entitled Intertextuality, the narrative of H. Wells in the work of Gabriela Aleman was proposed as an objective to study the intertextuality in the short story "El extraño viaje" of the Ecuadorian writer Gabriela Aleman, from the review of theoretical bases and comparative reading. For this purpose, it was essential to review Julia Kristeva's and Gerard Genette's proposals on intertextuality. On the one hand, Kristeva proposes the moments of absorption and transformation present in the constructive sequence of the text. And, on the other hand, Genette positions intertextuality as one of the five typologies of trans textual imbrications, presenting a redefinition of the term in his proposal. This qualitative research that sought to diagnose, explore, and describe the use of intertextuality as a resource in the construction of literary works had a bibliographic design. The method selected for the study was the hermeneutic method due to the interpretative nature required by the analysis. As instruments, literary and intertextual analysis cards were designed and applied, constructed based on different proposals. Among the main results achieved, the relationship found between the novel by H. Wells and the short story by Gabriela Aleman stands out. These results were obtained from the comparative reading of both texts. Other literary resources used in the construction of texts that make possible their credibility in the reader, as it happens in the plot of the work "El extraño viaje", were also discovered.